Towards a Metal-catalyzed Annulation Route to Pyridines and N-Hydroxy Pyrroles - Whitmore, Kenneth M. (Université d'Ottawa / University of Ottawa, 2012)
Despite progress in the metal-catalyzed synthesis of aromatic heterocycles, annulation routes towards 6-membered heterocycles remain underdeveloped. Specifically, routes towards pyridines are rare in spite of the prevalence of this moiety in novel drug candidates. Our initial efforts towards pyridines featured oximes as competent nucleophiles in the intramolecular, 6-exo dig annulation of alkynes using Brønsted acid catalysis. Two of the oxidation states required for subsequent aromatization are contained within the oxime via loss of water. An extension of this chemistry is presented and discussed, and involves the intramolecular metal-catalyzed 6-endo dig annulation of analagous alkynyl-oximes. Additionally, the discovery of a 5-exo dig annulation of related systems is discussed.
Keywords: Pyridine; Heterocycle; N-Hydroxy Pyrrole; Annulation; Catalysis; Metal